PENGELOLAAN PEMBELAJARAN DENGAN MENERAPKAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV SD - Harsini Harsini (Manajer Pendididikan, 2017)
The purpose of this study was to describe efforts to improve speaking skills and behavioral change Neger fourth grade students i09 District of Kepahiang with learning management applying the method of playing a role. Collecting data using test techniques, and nontes. The results showed that the average classical student the District 09 Elementary School kelasIV Kepahiang of the value of the first cycle to the second cycle to the third cycle has increased. Each cycle of implementation of the study obtained a value of 41.35 in the first cycle, and 62.65 in the second cycle and then the value of 76.5 in the third cycle. Asiswa berbicar skills improvement is also followed by changes in behavior and interests as well as student activity.